Willingness to Seek Treatment Among Black Students With Anxiety or Depression: The Synergistic Effect of Sociocultural Factors With Symptom Severity and Intolerance of Uncertainty. Issue 5 (September 2018) - Dean, Kimberlye E.; Long, Anna C.J.; Matthews, Russell A.; Buckner, Julia D.
Abstract: Anxiety and depressive disorders are among the most commonly diagnosed psychiatric disorders, yet they remain largely undertreated in the U.S. and Black adults are especially unlikely to seek or receive mental health services. Symptom severity has been found to impact treatment-seeking behaviors as have sociocultural factors. Yet no known research has tested whether these factors work synergistically to effect willingness to seek treatment. Further, emerging data point to the importance of transdiagnostic risk factors such as intolerance of uncertainty (IU). IU may be negatively related to seeking treatment given that Black adults may be uncertain whether treatment might benefit them. Thus, the current study examined the relations between symptom severity/IU and willingness to seek treatment for anxiety/depression problems and the impact of key sociocultural variables (i.e., cultural mistrust–interpersonal relations [CMI-IR], perceived discrimination [PED]) on these relations among 161 (85% female) Black undergraduates. Consistent with prediction, symptom severity was positively related to willingness, but unexpectedly, IU was positively related. There was a significant Symptom Severity × CMI-IR interaction such that severity was positively related to willingness among students with lower cultural mistrust, but not higher mistrust. There were also significant IU × PED interaction such that IU was positively related to willingness among students with lower PED, but not higher PED. Results highlight the importance of considering the interplay between symptom severity, transdiagnostic vulnerability factors, and sociocultural variables when striving to identify factors related to treatment seeking behaviors among anxious and/or depressed Black students. Highlights: IVs: symptom severity (SS) and intolerance of uncertainty (IU). SS is positively related to treatment seeking willingness among Black students. IU is positively related to treatment seeking willingness. SS-willingness relation occurs when cultural mistrust low. IU-willingness relation occurs when perceived discrimination low.